2005
DOI: 10.1159/000089966
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Lacuna Population Densities in Sheep, Elk and Horse Calcanei

Abstract: Osteocytes, the most prevalent cell type in bone, appear to communicate via gap junctions. In limb-bone diaphyses, it has been hypothesized that these cellular networks have the capacity to monitor habitual strains, which can differ significantly between cortical locations of the same bone. Regional differences in microdamage associated with prevalent/predominant strain mode (tension, compression, or shear) and/or magnitude may represent an important ‘variable’ detected by this network. This hypothesis was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 113 publications
2
13
0
Order By: Relevance
“…In view of other investigators' fi ndings that have shown that at least a portion of remodeling is targeted, we presume that other mechanotransduction pathways predominate in the equine radius and MC3. As discussed in our companion study [Skedros 2005], these can include innervation of bone and changes in the dendritic processes of osteocytes within canaliculi that are not associated with osteocyte death and changes in osteocyte lacunar density. However, we were only able to test some hypotheses indirectly; therefore, care must be taken when considering the present data in these contexts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of other investigators' fi ndings that have shown that at least a portion of remodeling is targeted, we presume that other mechanotransduction pathways predominate in the equine radius and MC3. As discussed in our companion study [Skedros 2005], these can include innervation of bone and changes in the dendritic processes of osteocytes within canaliculi that are not associated with osteocyte death and changes in osteocyte lacunar density. However, we were only able to test some hypotheses indirectly; therefore, care must be taken when considering the present data in these contexts.…”
Section: Resultsmentioning
confidence: 99%
“…However, the MC3s and radii exhibited opposite Ot.Lc.N/B.Ar differences in 'tension' versus 'compression' comparisons. As discussed in a companion study of regional Ot.Lc.N/B.Ar variations in artiodactyl and perissodactyl calcanei [Skedros, 2005], this difference may represent 'adaptations' in the relatively simple bending environment of the radius that are obscured by tissue adaptations of the more complex torsion/bending environment of the MC3.…”
Section: Osteocytic 'Operational' Network For Microdamage Detection:mentioning
confidence: 99%
“…Structurally, the tissues are easily visibly distinguished from one another by the presence and absence of osteocytes, but are more similar to each other in gross, histological morphology than they are to the more-studied cellular bone types of amniotes. In particular, differences in osteocyte presence and associated canalicular density are striking, even for the cellular boned carp where osteocytes are much less densely packed than those of birds and mammals (424 vs 700-1800cellsmm -2 ) (Li et al, 1991;Skedros, 2005). The low osteocyte density, coupled with the apparent relative scarcity of blood vessels in both tilapia and carp bone, make both fish bone types observed here appear, at lower magnifications, as more solid (less porous) blocks of tissue compared with amniote bone, also suggesting they may have a lower metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…elliptical in shape with major and minor diameters of 10 and 5m, respectively (McCreadie et al, 2004;Hannah et al, 2010)] the area fraction taken by the osteocytic lacunae in carp bones is 1.6%. The osteocytic lacunae (black arrows in Fig.3C,E) in the bones of the carp show distinct canalicular networks interconnecting adjacent lacunae (black arrowhead in Fig.3E); however, their distribution is less dense than in mammals (R.S., personal observation) (Skedros, 2005;Li et al, 1991).…”
Section: Osteocyte Distribution and Densitymentioning
confidence: 98%
“…The sheep and horses had been kept in large pastures. Calcanei were also obtained from 10 wild-shot skeletally mature male deer used in previous studies [Skedros et al, 1994a, b;Skedros, 2005].…”
Section: Calcanei Of Horses Elk Sheep and Deer ( Fig 7 )mentioning
confidence: 99%